EU's Policy of Disarmament as Part of its Normative Power - Roxana Hincu (CES Working Papers, 2015)
This article argues that EU's policy of Disarmament, Non-Proliferation, and Arms Export Control can be conceptualised into the framework of the normative power. Despite the EU strategies on this policy, such as EU Strategy against the proliferation of Weapons of Mass Destruction (2003), or Strategy to combat illicit accumulation and trafficking of Small Arms and Light Weapons (2005), the EU is far from being a unitary actor. In the international arena most actions on Disarmament and Non-Proliferation are enhanced by the United Nations and individually by each country that is a nuclear power. The measures taken by the EU in the international forums on Disarmament are analysed with a short historic overview on the issue and with a closer view on the EU's actions within the United Nations and those taken unilaterally.
Keywords: F5; F6; 330; disarmament; normative power; non-proliferation; foreign policy; security